LCA: Comparison Between Recycle and Reuse of Glass Beer Bottles - Teresa Mata (1999)
This work compares the life cycles of returnable and non-returnable beer bottles. The methodology, principles and framework adopted are those proposed by SETAC´s working group. The "Critical Dilution Volume" method is used to evaluate the inventory data and perform the environmental impact assessment. The inventory data was obtained from two Portuguese industries and compared with BUWAL database. The differences between returnable and one-way beer bottles were analysed to show that recycling of glass bottles provides larger environmental benefits than reuse.